Systematic Literature Review of Career Planning for Enhancing Among Indonesian Higher Education Student Work Readiness - Galfin Fudhail Faqih; Muhammad Firdaus; Anggi Pasca Arnu (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to systematically review the role of career planning in enhancing students' work readiness, particularly in response to the high unemployment rate among higher education graduates in Indonesia. Methodology: A systematic literature review (SLR) was conducted by identifying articles through Google Scholar using the Publish or Perish application. From 640 initial articles published between 2021 and 2025, 18 studies met the inclusion criteria and were analyzed through data extraction and synthesis. Results: The findings indicate that career planning is shaped by three main dimensions: individual factors, environmental factors, and academic factors. Findings: The results demonstrate that integrated career planning significantly contributes to improving students' work readiness. Novelty & Originality: This study offers a comprehensive conceptual framework that integrates fragmented findings from previous studies and provides practical implications for higher education institutions in developing structured career guidance programs to better prepare students for the labor market. Conclusions: The study concludes that structured career planning is essential for reducing graduate unemployment and enhancing workforce readiness. Type of Paper: This paper is a systematic literature review paper.